2013
DOI: 10.1111/1475-6773.12095
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Racial/Ethnic Disparities in Treatment across Episodes of Mental Health Care

Abstract: Objective To investigate disparities in mental health care episodes, aligning our analyses with decisions to start or drop treatment, and choices made during treatment. Study Design We analyzed whites, Blacks and Latinos with probable mental illness from Panels 9-13 of the Medical Expenditure Panel Survey, assessing disparities at the beginning, middle, and end of episodes of care (initiation, adequate care, having an episode with only psychotropic drug fills, intensity of care, the mixture of PCP and specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
146
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(153 citation statements)
references
References 67 publications
(124 reference statements)
7
146
0
Order By: Relevance
“…37,38 Prior studies exploring racial disparities in psychiatric care have suggested problems with access, inaccurate diagnoses, inadequate medication prescribing, and monitoring in racial minorities. 39,40 Specifically, decreased access to adequate MM care for patients of racial minorities has been reported in several studies. [41][42][43][44][45][46] Although these studies have explored differences in access to care and the financial benefits of eliminating disparities, to our knowledge, no prior study has demonstrated an interaction between cost of care and race in cancer patients with psychiatric comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Prior studies exploring racial disparities in psychiatric care have suggested problems with access, inaccurate diagnoses, inadequate medication prescribing, and monitoring in racial minorities. 39,40 Specifically, decreased access to adequate MM care for patients of racial minorities has been reported in several studies. [41][42][43][44][45][46] Although these studies have explored differences in access to care and the financial benefits of eliminating disparities, to our knowledge, no prior study has demonstrated an interaction between cost of care and race in cancer patients with psychiatric comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, persons with these disorders face increased rates of morbidity from general medical conditions [2][3][4] and a higher risk of premature mortality 5 . Among persons with mental disorders, disparities in quality and outcomes of care are more pronounced for racial/ethnic minorities [6][7][8] , and those from lower socio-economic status groups 9 . Severe mental illness (e.g., schizophrenia and bipolar disorder) is emerging as a prominent health disparity category, given estimates that persons in this group die 8-25 years younger than the general population 10,11 .…”
mentioning
confidence: 99%
“…However, disparities can also lead to inefficient patterns of service use (6). For example, because individuals from racial-ethnic minority groups often live in neighborhoods with fewer specialist mental health providers than are available in other neighborhoods (7) and because these individuals are less likely than whites to receive adequate mental health care (8), they may delay mental health treatment until they experience more acute symptoms and then may need more expensive care. In addition, misdiagnosis of mental disorders by primary care physicians may lead to unnecessary care (9).…”
mentioning
confidence: 99%
“…Wide racial-ethnic disparities in mental health care access are well documented (2,32,33). Once in treatment, Latinos have fewer mental health care visits than whites have, and blacks are more likely than whites to terminate care in acute psychiatric care settings (34).…”
mentioning
confidence: 99%